A randomised controlled trial of the clinical effectiveness and cost-effectiveness of the levonorgestrel-releasing intrauterine system in primary care against standard treatment for menorrhagia: the ECLIPSE trial - Gupta, Janesh K.; Daniels, Jane P.; Middleton, Lee J.; Pattison, Helen M.; Prileszky, Gail; Roberts, Tracy E.; Sanghera, Sabina; Barton, Pelham; Gray, Richard; Kai, Joe (NIHR Health Technology Assessment Programme, 2015)
Background: Heavy menstrual bleeding (HMB) is a common problem, yet evidence to inform decisions about initial medical treatment is limited.